Arbuscular mycorrhizas in the Larrea divaricata scrubland of the arid “Chaco”, Central Argentina - Lugo, M.A.; Anton, A.M.; Cabello, M.N. (International Journal of Agricultural Technology, 2005)
Arbuscular mycorrhizal root colonization and spore diversity were analyzed, in terms of seasons, dry and wet period and host species, in an arid secondary scrubland ecosystem (“Jarillal”) in Central Argentina. Larrea divaricata, dominant in this plant community, was the most colonized species followed by the grass Trichloris crinita (“herbaceous stratum fitness indicator”) whereas the lowest values were found in Sporobolus pyramidatus and Neobouteloua lophostachya (both of them “disturbance indicators”). Root colonization was closely related to host role in the community. The AMF diversity was low because of the disturbed features of “Jarillal” and arid conditions. Spore total density, specific spore density and spore richness were more related to the seasons and water availability than to the host species.